NeuroForm Atlas Stent-Assisted Coiling: Preliminary Results. Issue 1 (21st March 2018) - ten Brinck, Michelle F M; de Vries, Joost; Bartels, Ronald H M A; Grotenhuis, J André; Boogaarts, Hieronymus D
Abstract: BACKGROUND: Stent-assisted coiling (SAC) is increasingly being performed as intervention for wide-neck intracranial aneurysms. The NeuroForm Atlas Stent (CE-marked; Stryker, Kalamazoo, Michigan) is relatively new. OBJECTIVE: To evaluate the effectiveness and safety of NeuroForm Atlas SAC for intracranial aneurysms in the first such study. METHODS:  We retrospectively analyzed data from all patients treated with the NeuroForm Atlas SAC of an intracranial aneurysm, both ruptured and unruptured, between June 2015 and December 2016. Primary end-points were favorable clinical outcomes (modified Rankin scale score 0-2) and successful aneurysm occlusion (Raymond-Roy class I/II), both at 6-mo follow-up. Secondary end-points were the occurrence of intervention-related complications leading to permanent neurological deficit, the occurrence of intervention-related stroke and neurological death, immediate aneurysm occlusion, rupture (or rerupture) of the aneurysm, and recanalization. RESULTS: Twenty-seven consecutive patients, 10 with ruptured saccular wide-neck aneurysms, were treated with NeuroForm Atlas SAC. At 6-mo follow-up, 18/26 (69.2%) survivors had successful aneurysm occlusion and 22/26 (84.6%) had favorable clinical outcome. One patient had died of a cause unrelated to treatment. No intervention-related complications leading to permanent neurological deficit occurred. However, intraprocedural thromboembolic complications occurred in 4/27 patients (14.8%), and ischemic stroke related to treatment occurred in 4/26 (15.4%). No hemorrhagic complications were observed. CONCLUSION: NeuroForm Atlas SAC is a feasible way to treat ruptured and unruptured wide-neck aneurysms that are not amenable to conventional coiling or clipping. Aneurysm occlusion and favorable clinical outcome are consistent with previously reported rates for SAC of wide-neck aneurysms with other devices.